Somatostatin and Somatostatin-Containing Neurons in Shaping Neuronal Activity and Plasticity - Liguz-Lecznar, Monika; Urban-Ciecko, Joanna; Kossut, Malgorzata (Frontiers in Neural Circuits, 2016)
Since its discovery over four decades ago, somatostatin receives growing scientific and clinical interest. Being localized in the nervous system in a subset of interneurons somatostatin acts as a neurotransmitter or neuromodulator and its role in the fine-tuning of neuronal activity and involvement in synaptic plasticity and memory formation are widely recognized in the recent literature. Combining transgenic animals with electrophysiological, anatomical and molecular methods allowed to characterize several subpopulations of somatostatin-containing interneurons possessing specific anatomical and physiological features engaged in controlling the output of cortical excitatory neurons. Special characteristic and connectivity of somatostatin-containing neurons set them up as significant players in shaping activity and plasticity of the nervous system. However, somatostatin is not just a marker of particular interneuronal subpopulation. Somatostatin itself acts pre- and postsynaptically, modulating excitability and neuronal responses. In the present review we combine the knowledge regarding somatostatin and somatostatin-containing interneurons, trying to incorporate it into the current view concerning the role of the somatostatinergic system in cortical plasticity.